Muslim women's writing from across South and Southeast Asia - Jussawalla, Feroza F., 1953-; Omran, Doaa (Routledge, 2023)
"This essential collection examines South and Southeastern Asian Muslim women's writing and the ways they navigate cultural, political, and controversial boundaries. Providing a global, contemporary collection of essays, this volume uses varied methods of analysis and methodology, including: Contemporary forms of expression, such as memoir, oral accounts, romance novels, poetry, and social media, inclusion of both recognized and lesser-known Muslim authors, division by theme to shed light on geographical and transnational concerns, regional focus on Afghanistan, Pakistan, India, Bangladesh, Sri Lanka, Malaysia, and Indonesia"--